Conducting educational research : guide to completing a thesis, dissertation, or action research projec - Boudah, Daniel J. (Thousand Oaks Sage, 2020)
"Designed to be used during the research process, Conducting Educational Research: Guide for Completing a Major Project, Second Edition, walks readers through each step of a research project or thesis, including developing a research question, performing a literature search, developing a research plan, collecting and analyzing data, drawing conclusions, and sharing the conclusions with others. Throughout the book, Daniel J. Boudah covers all types of research (including experimental, descriptive, qualitative, group designs, and single subject designs) and helps readers link research questions to designs, designs to data sources and data sources to appropriate analyses. Each chapter includes activities and exercises to ensure the researcher is asking the right questions and producing a quality project"--
Research in education -- Identifying a research problem and question, and searching relevant literature -- Understanding relevant literature and writing a literature review -- Issues in validity and reliability -- Designing and conducting experimental research -- Designing and conducting qualitative research -- Designing and conducting descriptive research -- Creating a research proposal -- Analyzing and interpreting experimental research -- Analyzing and interpreting qualitative data -- Analyzing and interpreting descriptive research -- Writing research reports.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology